2018
DOI: 10.9734/ajaees/2018/39681
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Extension Services Delivery for Climate Change Adaptation by Crop Farmers in Niger State, Nigeria

Abstract: Agriculture mostly depends on weather and climate for optimum productivity. Climate change has become a global threat to agriculture and humanity. To cope with these changes, farmers employ adaptation strategies. This paper evaluates the Extension Service Delivery for Climate Change Adaptation by Crop Farmers in Niger State, Nigeria. Multistage sampling technique was used to randomly select 162 respondents. Data were analyzed using descriptive statistics and Likert-scale. The results showed that respondents we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…Approximately, all these constraints can be regarded as most serious constraints to rice production in the study area. Ebenehi et al, (2018) reported that inadequate fund hinders farmers from getting the necessary resources and technologies which assist to adapt successfully to climate change among crop farmers. Also, soil erosion problem and flood ranked 6 th ( 2.38), high cost of farm inputs ranked 7 th ( 2.36), lack of seed testing laboratories ranked 8 th ( 2.27), poor access roads and other infrastructure ranked 9 th ( 2.25), followed by absence/inadequate processing facilities ( 2.18), inadequate supply of farm inputs ( 2.17), lack of transport facilities ( and nonavailability of market for rice produce(…”
Section: Rice Farmer's Benefits Derived From Adoption Of Improved Tecmentioning
confidence: 99%
“…Approximately, all these constraints can be regarded as most serious constraints to rice production in the study area. Ebenehi et al, (2018) reported that inadequate fund hinders farmers from getting the necessary resources and technologies which assist to adapt successfully to climate change among crop farmers. Also, soil erosion problem and flood ranked 6 th ( 2.38), high cost of farm inputs ranked 7 th ( 2.36), lack of seed testing laboratories ranked 8 th ( 2.27), poor access roads and other infrastructure ranked 9 th ( 2.25), followed by absence/inadequate processing facilities ( 2.18), inadequate supply of farm inputs ( 2.17), lack of transport facilities ( and nonavailability of market for rice produce(…”
Section: Rice Farmer's Benefits Derived From Adoption Of Improved Tecmentioning
confidence: 99%
“…Adaptation methods can only be implemented if there is adequate funding to fund drought coping and adaptation strategies. Previous studies have noted that it is difficult for smallholder farmers to implement adaptation strategies recommended by agricultural advisors because of insufficient funding [30,31]. Smallholder farmers are often required to make financial commitments to drought adaptation and coping strategies, which include planting drought-tolerant varieties of crops and early maturing breeds of crops.…”
Section: Extension Services To Increase Drought-resiliencementioning
confidence: 99%
“…High incidence of flood is also a constraint that gives the farmers serious concern. [28] in his study, identified flood as a limiting constraint in adapting to climate change. Flood was identified as a common hazard in Europe which poses a problem presently, and will pose more problem in the future [32].…”
Section: Constraints In Using Viable Climatementioning
confidence: 98%
“…The peculiar land tenure system in the study area may not allow them to practice sustainable adaptation measures. High cost of improved and resistant varieties of crops as a major problem limiting farmers from adapting to climate change [28]. Conflict affects the farmers' ability to engage in farming activities which limits agricultural production in the study area.…”
Section: Constraints In Using Viable Climatementioning
confidence: 99%